Streetscapes-Matera - Siren, Pekka; Waligorska, Agnieszka (Mnémothèque Internationale des Sciences et Arts en Musique Électroacoustique, 1993)
Recording of Pekka Siren and Agnieszka Waligorska's Streetscapes-Matera. This work takes recordings of everyday life and add sounding provocations, including: train, elephants, jungle birds, Eskimos and laughing children, and a barking dog quartet. This imaginary mix was played in the streets with multiple speakers and recorded with peoples reactions. The final recording is a large demonstration of sounds mixing reality and imagination onto a canvas of sounds given back to the people.